Development of risky varices in alcoholic cirrhosis with a well-maintained nutritional status - Enomoto, Hirayuki (World J Hepatol, 2015)
AIM: To compare the nutritional status between alcoholic compensated cirrhotic patients and hepatitis C virus (HCV)-related cirrhotic patients with portal hypertension. METHODS: A total of 21 patients with compensated cirrhosis (14 with HCV-related cirrhosis and seven with alcoholic cirrhosis) who had risky esophageal varices were investigated. In addition to physical variables, including the body mass index, triceps skinfold thickness, and arm-muscle circumference, the nutritional status was also assessed using the levels of pre-albumin (pre-ALB), retinol-binding protein (RBP) and non-protein respiratory quotient (NPRQ) measured with an indirect calorimeter. RESULTS: A general assessment for the nutritional status with physical examinations did not show a significant difference between HCV-related cirrhosis and alcoholic cirrhosis. However, the levels of pre-ALB and RBP in alcoholic compensated cirrhotic patients were significantly higher than those in HCV-related compensated cirrhotic patients. In addition, the frequency of having a normal nutritional status (NPRQ ≥ 0.85 and ALB value > 3.5 g/dL) in alcoholic compensated cirrhotic patients was significantly higher than that in HCV-related compensated cirrhotic patients. CONCLUSION: According to our small scale study, alcoholic compensated cirrhotic patients can develop severe portal hypertension even with a relatively well-maintained liver function and nutritional status compared with HCV-related cirrhosis.